Tailored DC/Sputtered Niobium Oxide Properties for PEM Electrolysis Application. (14th September 2015) - Ion-Ebrasu, Daniela; Enache, Stanica; Rizoiu, Alexandru; Filip, Mihaela; Preda, Silviu; Varlam, Mihai; Fruth, Victor; Stefanescu, Ioan
Abstract : Proton exchange membrane (PEM) water electrolysis is seen as one of the most efficient and simple way to obtain high purity hydrogen. A major drawback in these systems is the catalysts long term stability in aqueous media. One way to improve that is to use niobium oxides as catalytic support since they have enhanced catalytic stability and high corrosion resistance to various acid-catalyzed reactions such as sulfonated radicals in the form of proton exchange membranes. In this work we show that nano-sized niobium-niobium oxides can be obtained by DC magnetron sputtering in Ar atmosphere, without using oxygen during deposition. Residual contamination with oxygen renders the films composite, consisting of niobium-niobium oxide conglomerates resembling to a core-shell structure. The catalytic activity of the top niobium-oxide layer is investigated by voltammetric methods whereas the structural, electrical and optical properties are studied by XRD, frequency dependent impedance and UV-Vis transmission techniques, respectively.